MUSEUM TRAINING TO DEVELOP THE SOCIAL AWARENESS OF CULTURAL IDENTITY IN A TIME OF UNIVERSALIZATION (Cadernos de Sociomuseologia, 2009)
The main theme of the ICTOP'94 Lisbon meeting is museum personnel training for the universal museum. At the very beginning it is important to identify what the notion universal museum can cover. It is necessary to underline the ambiguity of the term. On the one hand, the word 'universal' can be taken to refer to the variety of collected museum materials or museum collections, on the other hand it could refer to the efforts of the museum to be active outside the museum walls in order to achieve the integration of the heritage of a certain territory into a museological system. 'Universal' could also refer to the "new dimensions of reality: the fantastic reality of the virtual images, only existing in the human brain" (Scheiner 1994:7), which is very close to M. McLuhan's view of the world as a 'global village'. Thus, what is universal could be taken as being common and available to all the people of the world. 'Universal' can imply also the radical broadening of the concept of object: "mountain, silex, frog, waterfonts, stars, the moon ... everything is an object, with due fluctuations" (Hainard in Scheiner 1994: 7), which will cause the total involvement of the human being into his/her physical and spiritual environment. In the process of universalization, links between cultural and natural heritage and their links with human beings become more solid, helping to create a strong mutual interdependence.